Red Flour Beetle Response to Traps with Prior Captures - Smith, Colton; Campbell, James (My University, 2018)
The red flour beetle (Tribolium castaneum) is a major pest of food facilities such as flour mills and is often monitored using pitfall type traps with a food oil and pheromone attractant. Previous research had indicated that prior captures of beetles could increase beetle behavior captures in a trap. Here we used a more realistic bioassay to evaluate how the number of beetles previously captured include beetle captures in traps. Results showed no significant impact of prior captures on the number of red flour beetles captured in a trap. There were some trends suggested in the results that warrant further study to investigate, perhaps by focusing on individual beetle behavior at traps rather then using groups of beetles.
Keywords: Fall 2018